Regional record of a global anoxic event: OAE 1a on the Apulian Platform margin, Gargano Promontory, Southern Italy - LUCIANI V.; COBIANCHI, MIRIAM; LUPI, CLAUDIA (2006)
The Gargano Promontory of southern Italy, located on the eastern margin of the Apulia Platform, represents a peculiar Tethyan area where the transition between carbonate platform and adjacent basins is exposed on land. The Aptian stratigraphic record, represented in shallow-water, slope and deep-water deposits, provides a good opportunity to investigate the regional response to the worldwide documented climatic, biotic and palaeoceanographic changes related to Oceanic Anoxic Event 1a (OAE1a). A synthesis of data previously published (Ischitella and Coppitella sections), together with original data (Val Carbonara and Coppa della Guardia sections), from four stratigraphic sections from different depositional settings (proximal to distal) is provided, using an integrated, high-resolution micropalaeontological (planktonic foraminifera and calcareous nannofossils) and, for one section, geochemical (stable carbon and oxygen isotopes) approach. Organic matter preservation is confined to the more distal areas and consists of two thin intervals of black shales in the Aptian portion of the Marne a Fucoidi Formation. Biostratigraphic data assign the older black shale (5 cm thick) to the Selli Level equivalent (OAE1a, Lower Aptian); this carbon-rich interval is immediately followed by another black shale (7e10 cm thick) of early Late Aptian age. OAE1a is generally interpreted as a high-productivity event during a warming interval, followed by a cooling trend. In the Gargano Promontory, although the oxygen isotope curve indicates the above-mentioned climatic evolution, the micropalaeontological data do not support high fertility of the surface water, whereas micropalaeontological and geochemical data for the younger black shale do record high productivity (radiolarian increase in overall abundance, low nannofossil and foraminiferal species richness, increase in abudance of nannofossil fertility indices) associated with a cooling trend. The carbon and oxygen isotope record is in line with evidence from the curves documented ...